Long-range optofluidic control with plasmon heating - B. Ciraulo (Nature Portfolio, 2021)
Here, the authors combine digital holographic microscopy with thermoplasmonics in order to identify different contributions of thermally driven fluid dynamic phenomena. They find that local thermal perturbation leads to long-range changes in the dynamics of the system, and demonstrate an all-optical control strategy for microfluidic devices.